2018
DOI: 10.1002/jsfa.9138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold plasma on maintaining the quality of chub mackerel (Scomber japonicus): biochemical and sensory attributes

Abstract: The excellent antimicrobial efficacy of ACP treatment makes it a potential and promising alternative to other seafood preservation technology. This is the first report on the application of ACP to seafood, which is essential to perishable food storage. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 33 publications
6
34
0
Order By: Relevance
“…These microorganisms could play a role in spoilage of slices with extended storage time (Mol, Erkan, Uecok, & Tosun, ). TVBC and VPBC were found to increase in mackerel and herring after DBD‐HVCAP treatment during refrigerated storage (Albertos et al., ; Chen et al., ). The results suggested that DBD‐HVCAP treatment for at least 5 min was sufficient in augmenting the shelf‐life of Asian sea bass during 4 °C storage by retarding the growth of microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…These microorganisms could play a role in spoilage of slices with extended storage time (Mol, Erkan, Uecok, & Tosun, ). TVBC and VPBC were found to increase in mackerel and herring after DBD‐HVCAP treatment during refrigerated storage (Albertos et al., ; Chen et al., ). The results suggested that DBD‐HVCAP treatment for at least 5 min was sufficient in augmenting the shelf‐life of Asian sea bass during 4 °C storage by retarding the growth of microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…The disappearance of blue color judged titration termination. The PV were expressed as mill equivalents (meq) of active O 2 per kg of fat (Chen et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…It is encouraging that there is an increasing list of studies over the past five years demonstrating the antimicrobial properties of NTAP on fish [152,[155][156][157][158][159][160] and RTE seafood products [136,153,161,162], which can lead to the adoption of this method from the seafood industry. NTAP has a high potential to be commercially used within many fields of the seafood industry.…”
Section: Microbiological Quality and Safetymentioning
confidence: 99%